2020
DOI: 10.18502/avr.v29i1.2369
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of acceptable noise level in unilateral hearing aid users

Abstract: Background and Aim: It is well known that hearing aid fitting is an effective approach to improve the communication ability of hearingimpaired people. In the past, most of the hearing aids were fitted unilaterally rather than bilaterally. Whereas the unilateral hearing aid fitting improves verbal communication partially, it causes late-onset auditory deprivation. The main aim of this study is to investigate the ANL for each ear among the users with unilateral hearing aid experience. Methods: A total of 23 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…ANL was 5.5 ± 1.06. in GII unaided conditions, the range of ANL for GII was (6)(7)(8)(9)(10)(11)(12)(13)(14)(15) with a mean ± SD. 10.2 ± 2.82 and in aided, the ANL range was (9)(10)(11)(12)(13)(14)(15)(16)(17) with the mean ± SD. ANL 12.5 ± 2.82. there was a highly significant difference between regular unaided vs aided, regular aided vs irregular aided and regular aided vs irregular unaided (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ANL was 5.5 ± 1.06. in GII unaided conditions, the range of ANL for GII was (6)(7)(8)(9)(10)(11)(12)(13)(14)(15) with a mean ± SD. 10.2 ± 2.82 and in aided, the ANL range was (9)(10)(11)(12)(13)(14)(15)(16)(17) with the mean ± SD. ANL 12.5 ± 2.82. there was a highly significant difference between regular unaided vs aided, regular aided vs irregular aided and regular aided vs irregular unaided (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Many research addressed no significant correlation between audiogram configuration as well as ANL, yet based on jonas Brännström and Olsen, [16] findings, it exhibited significance. additionally, the ANL could exhibit greater values when the audiogram's slope is such that the average threshold before the 1 kHZ frequency exhibits significant variation from that of greater Frequencies [16,17] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that ANL can be a good predictor of hearing aid satisfaction; people with lower ANL have better suppression in the auditory efferent system and usually are more satisfied with their hearing aids [8]. The lower ANL indicates better noise tolerance [8][9][10][11][12][13]. The Persian version of this test was validated by Ahmadi et al using a running female-talker story with a 12-talker babble in children [12].…”
Section: Introductionmentioning
confidence: 99%